Laboratory Measure of Cheating Predicts School Misconduct. (25th March 2018) - Cohn, Alain; Maréchal, Michel André
Abstract: Laboratory experiments provide insights into the drivers of cheating behaviour, but it is unclear to what extent cheating in the laboratory generalises to the field. We conducted an experiment with middle and high school students to test whether a common laboratory measure of cheating predicts three types of school misconduct: ( i ) disruptiveness in class; ( ii ) homework non‐completion; and ( iii ) absenteeism. We find that students who cheat in the experimental task are more likely to misbehave at school, suggesting that experimental measures of cheating generalise to rule violating behaviour in naturally occurring environments.